Umbilical Cord Blood Use for Admission Blood Tests of VLBW Preterm Neonates: A Randomized Control Trial - Mu, Thornton S.; Prescott, Alicia C.; Haischer-Rollo, Gayle D.; Aden, James K.; Shapiro, Jonathan B. (American Journal of Perinatology, 2021)
Objective Umbilical cord blood (UCB) for admission laboratories is an approach to decrease anemia risk in very low birth weight (VLBW) neonates. We hypothesized that UCB use results in higher hemoglobin concentration [HgB] around 24 hours of life.Study Design A randomized control trial among VLBW infants whose admission laboratories were drawn from UCB (n = 39) or the infant (n = 41) in three U.S. military NICUs (clinicaltrials.gov#NCT02103296).Results No demographic differences were observed between groups. UCB infants had higher [HgB] at 12 to 24 hours of life (15.5 vs. 14.0 g/dL, p = 0.02). The median time to first transfusion was 17 days longer in the experimental group (p = 0.04), and at discharge, their number of donor exposures was lower (1.1 vs. 1.8, p = 0.04).Conclusion In the first 24 hours of life that is a period of higher risk for hemodynamic instability, UCB utilization for admission bloodwork in VLBW infants results in higher [HgB].Key Points
Keywords: umbilical cord blood; preterm infant; anemia of prematurity; hemoglobin; blood transfusion